SERAT WEDATAMA DALAM PERSPEKTIF TATTWA DAN SUSILA HINDU - Mardwiatmoko, Mardwiatmoko (Fakultas Dharma Duta dan Brahma Widya, 2024)
The Javanese literary work Serat Wedatama is one of the historical relics in the form of culture written by KGPAA Mangkunegara IV. Judging from the author's fact that he still has blood ties with the Hindu kings of Majapahit and also seen from the selection of vocabulary that contains Sanskrit elements, it is alleged that this literary work has a correlation with the Hindu concept. This research aims to find out the values of Serat Wedatama in the perspective of Hindu tattwa and ethics. The method used in this study is a literature study with a hermeneutic approach. The results of the study show that Pupuh Pangkur Pada 12 in the Hindu perspective is the concept of Tattwa Jnana or Brahma Widya, moksa, Bhiksuka/Sannyasin, and brahmin. Pupuh Pucung Pada 12 is the concept of Bhatara and Paramatma. Pupuh Sinom Pada 1 is identical to the sloka in Lontar Sila Sasana which contains the concept of precepts, besides that the pupuh also implies the teaching of tat twam asi. Pupuh Sinom on 3 is the implementation of the Siwaratri brata.